2013 Curriculum Management at Yogyakarta State High School 2, Indonesia - Deby Marsadina; Cepi Safruddin Abd Jabar (Kusuma Negara Business School, 2020)
Curriculum management is one of the instrumental aspects for the success of teaching and learning to achieve a goal in education. This study aims to analyze how the existing curriculum management in Yogyakarta 2 Public High Schools. The method uses in this study is qualitative approach with descriptive methods. The data collecting technique in this study was observation, interview and documentation. The data analysis in this study was performed by data reduction, data presentation and conclusion drawing. The results showed that 1. Curriculum planning includes socialization of the curriculum in a workshop, compiling annual programs, compiling semester programs, and compiling lesson plans. 2. The implementation of the curriculum is supported by adequate infrastructure, the development of learning implementation plans, the socialization provided by the school principal, participation in the subject teacher training (MGMP) training and implementing the learning implementation plan. 3. Curriculum evaluation includes students, teachers, teaching media which are assessed by the school principal, supervision, and assessors who are competent in their field. The conclusion of this study curriculum management which includes 3 aspects namely planning, implementation and evaluation by looking at the conditions that exist in schools.